(untitled) - United Nations Development Programme (UNDP) (Ha noi, 2008)
This report focusses on the legal framework directly influencing the business and investment environment, namely implymentation of the enterprise law and investment law.
Keywords: Business; Business law; Luật kinh doanh,Kinh doanh; Việt Nam,Vietnam